Two Faces of Exclusion : The Untold History of Anti-Asian Racism in the United States - Kurashige, Lon, 1964- (Book collections on Project MUSE., 2016)
From the Chinese Exclusion Act of 1882 to Japanese American internment during World War II, the US has a long history of anti-Asian policies. But Lon Kurashige demonstrates that despite widespread racism, Asian exclusion was not the product of an ongoing national consensus, it was a subject of fierce debate. This book examines the opposition to discrimination that involved some of the most powerful public figures in America.